The witch of Portobello : a novel - Coelho, Paulo (HarperCollinsPublishers, 2007)
Traces the life of Athena, an abandoned daughter of a Transylvania gypsy, in a tale told from the viewpoints of such characters as her adoptive journalist mother, a teacher of calligraphy, and an actress.